Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.29252/rbmb.9.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ischemia-Modified Albumin, Fibrinogen, High Sensitivity C- Reactive Proteins in Type-2 Diabetes Mellitus without Hypertension and Diabetes Mellitus with Hypertension: A Case-Control Study

Abstract: Background:The objective of this study was to determine the levels of serum ischemia-modified albumin (IMA), fibrinogen (FIB) and high sensitivity C-reactive protein (hs-CRP) in type 2 diabetes mellitus (T2DM) patients with hypertension (HT) (DMT2HTN) and without HT (DMT2). Also, their association with certain biochemical and physical factors were studied to identify possible risk factors that lead to cardiovascular complications. Methods: Fasting blood samples were collected from 35 DMT2 or DMT2HTN patients e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Similarly, Sushith S et al reported a higher level of BMI in hypertensive versus non-hypertensive patients with type 2 diabetes. 32 Consistent with our results, Luo et al revealed that Ag-RP neuropeptide might be a potent mediator between appetite and obesity state. 5 Also, similar to the study by Masoodian et al, there was no significant difference in glycemic markers and lipid profile between different BMI tertiles 33 Based on our findings, Ag-RP and α-MSH levels were higher among higher tertiles of BMI; other evidence has also indicated that obese adults have elevated plasma levels of α-MSH and Ag-RP.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Sushith S et al reported a higher level of BMI in hypertensive versus non-hypertensive patients with type 2 diabetes. 32 Consistent with our results, Luo et al revealed that Ag-RP neuropeptide might be a potent mediator between appetite and obesity state. 5 Also, similar to the study by Masoodian et al, there was no significant difference in glycemic markers and lipid profile between different BMI tertiles 33 Based on our findings, Ag-RP and α-MSH levels were higher among higher tertiles of BMI; other evidence has also indicated that obese adults have elevated plasma levels of α-MSH and Ag-RP.…”
Section: Discussionsupporting
confidence: 93%
“…Analyses of clinical and experimental investigations have shown that types one and two DM (DM1 and DM2) are associated with an increase in IMA, the level of which depends on glucose concentration, presence of complications, and comorbidities [125][126][127][128][129]. On the other hand, the formation of IMA in the early stages of DM plays a significant role in the pathogenesis of diabetic complications.…”
Section: Diabetes Mellitus and Itsmentioning
confidence: 99%
“…High levels of these proteins are a sign of a recent heart attack. One of the markers of heart attack is the Cardiac Troponin-T. Other biomarkers include fibrinogen and PAI-1, high levels of homocysteine, elevated asymmetric dimethylarginine, and elevated brain natriuretic peptide (also known as B-type) (BNP) [19,20].…”
Section: Introductionmentioning
confidence: 99%